Replotting marriage in nineteenth-century British literature - Galvan, Jill Nicole, 1971-; Michie, Elsie B. (Elsie Browning), 1948- (Columbus : The Ohio State University Press, 2018)
"This volume puts marriage in conversation with many aspects of culture--education, anthropology, Darwinism, crime, and more--widening the repertoire of questions scholars ask about fictional coupling. Attending closely to genre and narrative, it analyzes the marriage story as formally diverse rather than a familiar plot line"--
The Bildungsroman, the romantic nation, and the marriage plot / Ian Duncan -- Darwin's marriage plots: unplotting courtship in late Victorian fiction / Elisha Cohn -- Mythic marriage: Haggard, Frazer, Hardy, and the anthropology of myth / Kathy Psomiades -- Playing the princess: enacting and resisting marriage in the Victorian school story / Kelly Hager -- The longue durée of political Bildungsromane: putting George Eliot into dialogue with Danish television / Lauren M.E. Goodlad -- 'Til death do us part: marriage, murder, and confession / Marlene Tromp -- Marriage, modernity, and the transimperial / Sukanya Banerjee -- "Even supposing-": reading/writing outside the marriage plot in Dickens fan fiction / Holly Furneaux -- Disabling marriage: communities of care in Our mutual friend / Talia Schaffer -- Extra man: dining out beyond the marriage plot in Our mutual friend / Helena Michie -- Afterword: Real figures / Mary Jean Corbett.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed May 18, 2018).
JSTOR
Keywords: Marriage in literature; English fiction -- 19th century -- History and criticism; English literature -- 19th century -- History and criticism; Mariage dans la littérature.; Roman anglais -- 19e siècle -- Histoire et critique; Littérature anglaise -- 19e siècle -- Histoire et critique; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY COLLECTIONS -- General; English fiction; English literature; Marriage in literature; 1800-1899; Criticism, interpretation, etc; Electronic books